21. GUIDELINES FOR ANALYZING THE GENETIC POLYMORPHISM OF PLASMODIUM FALCIPARUM AND PLASMODIUM VIVAX BASED ON WHOLE-GENOME SEQUENCING DATA (Vietnam Journal of Community Medicine, 2025)
Objective: This study provides a guideline for analyzing the genetic polymorphism of Plasmodium falciparum and Plasmodium vivax using whole-genome sequencing data.Research methods: A standardized workflow for genomic data analysis was applied, including variant calling (SNPs, InDels) from raw sequencing data, variant annotation and classification, phylogenetic tree construction and population structure analysis, and association analysis between genetic variants and antimalarial drug resistance.Results: The total number of SNPs detected ranged from 50,000-80,000 in P. falciparum and 40,000-60,000 in P. vivax, while InDels varied between 5,000 and 15,000. The pfcrt (72-76 CVIET) mutation associated with Chloroquine resistance was highly prevalent, reaching 92.7% (51/55) in 2017-2018 and 91.1% (72/79) in 2019-2020 in Vietnam, whereas its prevalence in Africa was significantly lower (< 5%) due to the transition to Artemisinin-based treatments. The k13 C580Y mutation, a key marker of Artemisinin resistance, was most frequently observed along the Thailand - Cambodia border (60%). In Vietnam, the mutation had a prevalence of 82% (41/50), indicating the regional spread of resistant strains within Southeast Asia. Notably, the pfmdr1 copy number variation (> 1.5 copies), associated with Mefloquine resistance, was detected in 23.6% (13/55) of cases in 2017-2018, but this decreased to 1.3% (1/79) in 2019-2020 in Vietnam.Conclusion: The application of whole-genome sequencing combined with advanced bioinformatics approaches provides crucial insights into the genetic polymorphism of malaria parasites, supporting drug resistance surveillance and informing more effective malaria control strategies.
Keywords: Plasmodium falciparum; Plasmodium vivax; genetic polymorphism; whole-genome sequencing; drug resistance